Tumoral and paratumoral NK cells and CD8+ T cells of esophageal carcinoma patients express high levels of CD47 - Strizova, Zuzana; Vachtenheim, Jiri; Snajdauf, Martin; Lischke, Robert; Bartunkova, Jirina; Smrz, Daniel (Scientific reports, 2020)
In a limited number of human malignancies, anti-CD47 therapy leads to the rapid clearance of tumor cells by macrophages. In esophageal squamous cell carcinoma, anti-CD47 treatment has shown promising results in vitro. However, the CD47 expression pattern in tumor-infiltrating lymphocytes (TILs), which are associated with prolonged overall survival and serve as a positive prognostic factor, is largely unknown. In this study, a total of 36 tissue samples from the tumor, peritumoral tissue, and adjacent healthy esophageal tissue was obtained from 12 esophageal carcinoma (EC) patients, and the surface expression of CD47 was evaluated in natural killer (NK) cells, CD8+ T cells, and the nonlymphocyte cell fraction. We found that the proportions of the evaluated cells and their CD47-expressing populations were comparable across the analyzed tissue compartments. However, the proportions of CD47-expressing populations in the analyzed tissue compartments were significantly higher in NK cells and CD8+ T cells than in the nonlymphocyte cell fraction. Importantly, the intensity of CD47 staining was also significantly higher in the tested immune cells than in the nonlymphocyte cell fraction. High expression of CD47 in tissue-infiltrating NK cells and CD8+ T cells in EC patients can, therefore, affect the efficacy of anti-CD47 therapy in EC.
Keywords: regulace genové exprese u nádorů; tumor infiltrující lymfocyty; Female; skvamózní karcinom jícnu; CD47 Antigen; ženské pohlaví; Gene Expression Regulation, Neoplastic; Lymphocytes, Tumor-Infiltrating; buňky NK; lidé; Esophageal Neoplasms; CD8-Positive T-Lymphocytes; Carcinoma; karcinom; nádory jícnu; Male; CD8-pozitivní T-lymfocyty; Aged; Killer Cells, Natural; antigeny CD47; Esophageal Squamous Cell Carcinoma; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans